2023
DOI: 10.1002/cbf.3774
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D and lactoferrin attenuate stress‐induced colitis in Wistar rats via enhancing AMPK expression with inhibiting mTOR–STAT3 signaling and modulating autophagy

Abstract: Irritable bowel syndrome (IBS) is a global gastrointestinal disorder closely related to psychological stress exposure and local colonic inflammation. Herein, we investigated the effect of wrap‐restraint stress (WRS) on rat behavior, on adenosine monophosphate‐activated protein kinase–mammalian/mechanistic target of rapamycin–signal transducer and activator of transcription 3 (AMPK–mTOR–STAT3) signaling, and autophagy in colonic mucosa. The impact of chronic administration of vitamin D3 and lactoferrin was comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 68 publications
0
5
0
Order By: Relevance
“…In recent years, more and more animal experiments have revealed the presence of a large number of autophagic vesicles accompanied by mitochondrial vacuolization in DSS-induced colitis. In Wistar rats, vitamin D has been shown to alleviate stress colitis through mTOR-STAT3 signaling and regulation of autophagy[ 34 ]. Similarly, we found that activation of estrogen receptor β, which is highly expressed in intestinal tissues, can inhibit colitis by promoting NLRP6-mediated autophagy[ 35 ].…”
Section: Atg Mutations and Intestinal Inflammationmentioning
confidence: 99%
“…In recent years, more and more animal experiments have revealed the presence of a large number of autophagic vesicles accompanied by mitochondrial vacuolization in DSS-induced colitis. In Wistar rats, vitamin D has been shown to alleviate stress colitis through mTOR-STAT3 signaling and regulation of autophagy[ 34 ]. Similarly, we found that activation of estrogen receptor β, which is highly expressed in intestinal tissues, can inhibit colitis by promoting NLRP6-mediated autophagy[ 35 ].…”
Section: Atg Mutations and Intestinal Inflammationmentioning
confidence: 99%
“…Reportedly, a dose of 500 IU/kg of vitamin D for 14 days in rats alleviated stress-induced colitis 41 . AMPK and STAT3 play a role in the immune system, with AMPK responsible for shifting macrophages to the anti-inflammatory M2 phenotype and STAT3 activating AMPK via IL-10 regulation 41 . mTOR is a serine/threonine kinase that regulates cell proliferation, apoptosis and autophagy through multiple pathways 42 .…”
Section: Vitamin D Mechanism Of Actionmentioning
confidence: 99%
“…mTOR is a serine/threonine kinase that regulates cell proliferation, apoptosis and autophagy through multiple pathways 42 . AMPK is thought to alleviate colitis by repairing the colonic intestinal barrier and its tight junction proteins once induced by IL-10 41 . The vitamin D-treated groups demonstrated a significant increase in the serum levels of AMPK and IL-10 and a decrease in STAT3.…”
Section: Vitamin D Mechanism Of Actionmentioning
confidence: 99%
See 2 more Smart Citations